Marine natural products as innovative cosmetic ingredients - Fonseca, Sara (2023)
Over the course of the last 20 years, numerous studies have identified the benefits of an array of marine natural ingredients for cosmetic purposes, as they present unique characteristics not found in terrestrial organisms. Consequently, several marine-based ingredients and bioactive compounds are under development, used or considered for skin care and cosmetics. Despite the multitude of cosmetics based on marine sources, only a small proportion of their full potential has been exploited. Many cosmetic industries have turned their attention to the sea to obtain innovative marine-derived compounds for cosmetics, but further research is needed to determine and elucidate the benefits. This review gathers information on the main biological targets for cosmetic ingredients, different classes of marine natural products of interest for cosmetic applications, and the organisms from which such products can be sourced. Although organisms from different phyla present different and varied bioactivities, the algae phylum seems to be the most promising for cosmetic applications, presenting compounds of many classes. In fact, some of these compounds present higher bioactivities than their commercialized counterparts, demonstrating the potential presented by marine-derived compounds for cosmetic applications (i.e., Mycosporine-like amino acids and terpenoids’ antioxidant activity). This review also summarizes the major challenges and opportunities faced by marine-derived cosmetic ingredients to successfully reach the market. As a future perspective, we consider that fruitful cooperation among academics and cosmetic industries could lead to a more sustainable market through responsible sourcing of ingredients, implementing ecological manufacturing processes, and experimenting with inventive recycling and reuse programs.